Conversational Implicature In Advertisement Slogans Embedded With Sexual Content: A Lecturer Analysis In Business Class - Kadek Adyatna Wedananta; Putu Kerti Nitiasih; Atima Kaewsa-ard (Soshum: Jurnal Sosial dan Humaniora, 2020)
As a lecturer in a business class, it might be interesting to dig deep to advertisement slogan embedded with sexual content like Condoms advertisement. This advertisement uses implicit language in the way they promote the product because it mostly leads to free sex. Therefore, the phenomenon of advertisers creatively uses the implicit slogans to attract their customers about their product might be interesting to discuss. This study aims to investigate the use of conversational implicature and the violation of cooperative principle or maxims occurred in condoms advertisement slogan and investigate the perception of business class students toward the analysis of this advertisement slogan to learn. It was descriptive qualitative research with 15 condoms advertisement slogans to be analyzed and 15 business class students to be interviewed. The result came with 100% particularized implicature used, 100% of violating of maxim of quantity, 100% of violating of maxim manner, 73 % of violating maxim of quality, and no violation in maxim of relevance. In conclusion, advertisers are using particularized implicature and violation of some cooperative principles or maxims to avoid informative messages in promoting their product (condom) which is banned in their advertisement rule. However, the advertisers keep making the slogans relevant to the products, so that some particular people can easily understand the message conveyed by the slogans. Moreover, the business class students agreed that this analysis should be important to learn because they will work as an entrepreneur who thinks about utterances in creating slogans for advertisement, especially sexual content. Further research should analyze more slogans in sexual content and use more techniques of analysis.